Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages But in June 1935 the cost of the British Medical Association minimum diet was 7/- per man-value. (Man-value denotes unit man value. Women and children are represented by fractions of unity.) The British Medical Association Nutrition Committee laid down, that health and working capacity could not be maintained on less than the amounts of the various foodstuffs making up this minimum list. Families who do not, or cannot, spend on food the amounts that are required to purchase that diet cannot be adequately nourished. The public conscience is sometimes lulled by statements that ignorance of food values and of cooking is the main cause of malnutrition. These statements are untrue, and cast an undeserved slur upon the capacity of the working-class housewife. There are, and there always will be, some few people who cannot manage their household affairs and these are not only to be found among the poor ; but the generality of working women are capable and efficient. They, by rule-of-thumb methods, buy, so far as their incomes permit them, food for their families which is suitable both in quantity and kind. The tragedy lies in the fact that after rent, fuel and light, clothing and boots, insurances, etc., have been provided for, there remains from the "dole", or from a low wage, insufficient to purchase a safe and satisfactory diet for the family. Unless the purchasing power is adequate, deficiencies in diet must occur and malnutrition result, for items of expenditure other than food can rarely be reduced. Food has many other functions to perform than merely to fill the stomach and stay the pangs of hunger. A satisfactory diet on which children can grow, and which will maintain health and working capacity, 10 15X/2/217/2